Esther Greenwood's colonization seen through the prism of the Bildungsroman - Damljanović Nataša V. (University of Kragujevac - Faculty of Pedagogy, Užice, 2018)
Early and mid-20 th century is a period in literature which deals with the phenomenon called a "new woman". The goal of this paper is to analyze Sylvia Plath's novel, The Bell Jar-the psychological growth/maturation of the novel's heroine-Esther Greenwood. To observe all the obstacles she faces on her developmental trajectory. To show her sufferance and nonconformity, to the feminine ideals set by male expectations in postwar America. Moreover, to depict the mere process of colonization of her soul, her body by her mother and the country she lives in by imposing full or partial control over her. Therefore, colonialism in Esther's case, metaphorically speaking, mainly takes the form of lack of privilege in organizing the day to day events of her creative life. The novel The Bell Jar consists of the plot narrated in the first person singular overloaded with and organized around a countless number of accidents. The theory of the Bildungsroman/the female Bildungsroman can help us to map those events, especially in her childhood and early adolescence, which caused traumas that have shaped her life. The rebellious nature she possesses cannot possibly be associated with "madness" of any kind but the fact that she is an educated, young lady who sees the world with different eyes. The width of her education doesn't allow her to use the kaleidoscope in observing the everyday life. For this hypothesis we have used the methodologies of theoretical and cultural analysis of the main as well as all the others characters who have directly or indirectly influenced her coming of age.